Differentiation of the content of classes on physical education, taking into account indicators of physical health and physical preparedness of students in grades 7-9 - Margarita Mameshina (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to study changes in the physical health indicators of students in grades 7-9 under the influence of a differentiation program for the content of physical education classes. Material & Methods: analysis and generalization of scientific and methodological literature; study of documentary materials and systematization of information; pedagogical observation; biomedical methods; pedagogical testing; methods of mathematical statistics. Results: according to the results of the initial study, the "average" level of physical health of schoolchildren of 7th grades was determined, "below the average" - for students of 8-9th grades and the "low" level of physical preparedness of the studied contingent. Conclusions: the revealed and significant changes (p<0,05-0,001) of indicators of physical health and physical preparedness of students in grades 7-9 of the main groups indicate the effectiveness of the proposed program for differentiating the content of physical education classes.